Implementation Implementation Of Public Service Policies At The Department Of Investment And Integrated One Door Service at Pringsewu Regency - Ramadan , Faridz; Wardhani , Andi Corry; Malta, Malta (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2023)
Purpose - Policy implementation is an important step in the policy process, but the policies that have been prepared have failed in their implementation. This study aims to find out how the process, actors who play a role, supporting factors, and inhibiting factors formulate an ideal model to be implemented in the Pringsewu Regency PMPTSP Service. Methodology - This research method uses a descriptive qualitative approach using the theory of Daniel A. Mazmanian and Paul A. Sabatier 1983 with attention to the characteristics of problems, policies, and the environment to examine the implementation of policies in the PMPTSP Office of Pringsewu Regency. Findings - The results of this study state that the policy implementation process needs to be simplified, standardized procedures and aligned with the above policies, factors that support policy implementation, namely by developing and formulating policies and simplifying investment regulations starting from business sectors and priority areas, while factors that hinder implementation policies, namely changes in regulations related to investment and changes in licensing services which are very dynamic. Originality - the researcher recommends a policy implementation model as the research results found by researchers, namely the D7K model (Disruption, Communication, Consolidation, Correlation, Comparison, Collaboration, Compassion, and Control).